The effects of ACE inhibition on central retinal artery in diabetes mellitus - Celebi, S.; Celiker, H.; Celebi, H.; Celiker, U.O. (My University, 1998)
Angiotensin converting enzyme (ACE) inhibitors have been known to inhibit the effects of angiotensin II which increases the vascular resistance. In this study, we studied the acute effects of a single dose of 2.5 mg oral cilazapril, ACE inhibitor on blood flow velocity and vascular resistance parameters of central retinal artery (CRA) by color Doppler ultrasonography in 17 patients with nonproliferative diabetic retinopathy (NPDR) and compared the effects of the drug with a placebo group including 17 patients with nonproliferative diabetic retinopathy. After cilazapril medication, peak systolic blood flow velocity of central retinal artery didn't change, while peak diastolic and mean blood flow velocity increased (p<0.05, p<0.05). Significant decrease in pulsatility and resistivity indices of the vessel were observed (p<0.05, p<0.05). Cilazapril decreases the resistance parameters of CRA which nourishes one of the target tissues of diabetic retinopathy.
Keywords: Central retinal artery; Cilazapril; Color Doppler imaging; Diabetes retinopathy